Activation of Krox20 gene expression by Sox10 in myelinating Schwann cells. - Reiprich, Simone; Müller, Jana; Wegner, Michael; et al. (Journal of Neurochemistry, 2010)
The high-mobility group domain transcription factor Sox10 is believed to influence myelination in Schwann cells by directly activating myelin genes and by inducing Krox20 as a pivotal regulator of peripheral myelination. Krox20 induction at this stage is thought to be mediated by the myelinating Schwann cell element 35 kb downstream of the Krox20 transcriptional start site and requires cooperation with Oct6. Here, we prove for the first time in vivo that Schwann cell-specific Krox20 expression indeed depends on Sox10. We also provide evidence that Sox10 functions through multiple, mostly monomeric binding sites in the myelinating Schwann cell element in a manner that should render the enhancer exquisitely sensitive to Sox10 levels. Synergistic activation of the enhancer by Sox10 and Oct6 furthermore does not involve cooperative binding to closely spaced binding sites in defined composite elements. Nevertheless, the POU domain of Oct6 and the high-mobility group domain of Sox10 as the two DNA-binding domains were both essential indicating that each transcription factor has to bind independently to DNA. Whereas the POU domain was the only important region of Oct6, two further Sox10 domains were required for synergistic Krox20 activation. These were the carboxyterminal transactivation domain and the conserved K2 domain in the central portion of Sox10. All required regions are conserved in several closely related POU and Sox proteins thus explaining why Oct6 and Sox10 can be replaced by their relatives during Krox20 induction in myelinating Schwann cells. © 2009 International Society for Neurochemistry.
UnivIS-Import:2015-03-09:Pub.2010.med.IB.LPCIPDBI.activa
Keywords: Glia; High-mobility group; Neural crest; Peripheral nervous system; POU; Transcription factor